2013
DOI: 10.1091/mbc.e12-12-0885
|View full text |Cite
|
Sign up to set email alerts
|

JNK1/2 regulates ER–mitochondrial Ca2+ cross-talk during IL-1β–mediated cell death in RINm5F and human primary β-cells

Abstract: JNK1/2 has an obligatory role in mediating IL-1β–induced endoplasmic reticulum calcium release, its uptake into the mitochondria, and consequent apoptotic cell death in pancreatic β-cells. This is accompanied by attenuation of glucose-stimulated insulin release and abrogation of this event in the presence of JNK1/2 siRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…4). The observations we have made in our diabetic embryopathy model system agree with findings in another recent study, which showed that inhibiting JNK1/2 prevented ER stress and apoptosis in pancreatic cells 130 . Therefore, our work has indicated a reciprocal causation between JNK1/2 and ER stress exists in pathogenesis of diabetic embryopathy (Fig.…”
Section: The Reciprocal Causation Between Jnk1/2 Activation and Er Stsupporting
confidence: 92%
“…4). The observations we have made in our diabetic embryopathy model system agree with findings in another recent study, which showed that inhibiting JNK1/2 prevented ER stress and apoptosis in pancreatic cells 130 . Therefore, our work has indicated a reciprocal causation between JNK1/2 and ER stress exists in pathogenesis of diabetic embryopathy (Fig.…”
Section: The Reciprocal Causation Between Jnk1/2 Activation and Er Stsupporting
confidence: 92%
“…Intracellular calcium levels were measured as described in the Fluo-4 Direct Calcium Assay kit (F10472, Invitrogen). 56 After seeding 5 Â 10 5 cells in 96-well plates, the medium was removed and 50 ml of prewarmed HBSS were added. The Fluo-4 Direct calcium reagent was prepared as described and added in a final concentration of 2.5 mM to the plate wells containing HBSS.…”
Section: Methodsmentioning
confidence: 99%
“…IL-1β is considered an important endogenous cytokine that can induce β-cell apoptosis and lead to the onset of diabetes by various pathways such as NO, 16 Ca2 + , 17 mitochondrial membrane potential, ROS 18 and endoplasmic reticulum stress (ERS). 19 The pro-apoptotic effect of IL-1β was observed in MIN 6 islet cells, which are mouse tumor cells expressing SV40 large T antigen under the control of an insulin promoter. Therefore, IL-1β-induced apoptosis has been used to evaluate disease mechanisms and potential treatment strategies for diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism may be attributed to the inhibition of the NF-kB pathway, limiting the release of pro-inflammatory cytokines and reducing lipid peroxidation in the heart of diabetic animals. 19 In addition, EGCG has strong antioxidant activity, which can prevent or T2DM and complications by scavenging oxygen-free radicals and improving OS. Myung-Kwan Han's study revealed that EGCG can combat IL-1β-induced RINm5F cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%